Synergy between recombinant endoglucanase a and exoglucanase s secreted by bacillus subtilis WB800N - Ngọc Phương, Nguyễn Hoàng; Toàn, Võ Minh; Vương, Lê Dương; Phương Trang, Phan Thị; Thước, Trần Linh; Hoàng, Nguyễn Đức (Vietnam Journal of Biotechnology, 2018)
An approach for dertemining the synergistic activity of cellulosomal catalytic units in culture media is among essential steps in the research of artificial cellulosomes. Endoglucanase A (CelA) and exoglucanase S (CelS) are two abundant cellulosomal cellulases secreted by anaerobic thermophilic bacterium Clostridium thermocellum and mostly responsible for the cellulolytic activities. They are the well-known candidates of catalytic units for artificial mini-cellulosome. Their synergistic activities play important roles in cellulolytic degradation. CelA cleaves inside the cellulose chains and produces more chain ends for the next step controlling by CelS. While endoglucanase demonstrates distinct activity on carboxymethyl cellulose, it still lacks the specific substrate for quantifying exoglucanase activity. In this research, we introduced an approach for measuring the synergistic activity for these endo and exoglucanase. We designed two recombinant proteins CelA and CelS secreted by the host-cell Bacillus subtilis WB800N in order to investigate their synergistic activity in culture media. The secretory expression was confirmed by tandem mass spectrometry. A modified dinitrosalicylic acid assay was performed on 96 well-plate for quantifying cellulolytic activities of the secreted cellulases in culture media. When adding CelA into CelS, CMCase activities were enhanced and higher than the total of their individual CMCase activities at some cases. When mixing 3 of CelA with 5 of CelS, the CMCase activity was enhanced about 35.5% of the total activities from individual ones. This indicated the synergistic activity of the endo and exoglucanase could degrade cellulose more efficiently than their individual activities. The research also provides the essential materials and methods for further research on designing mini-cellulosome secreted by B. subtilis